조선시대 역사지진자료를 이용한 경주와 포항의 최근 지진규모 예측 - 김준철; Jun Cheol Kim; 권숙희; Sookhee Kwon; 장대흥; Dae-heung Jang; 이근우; Kun Woo Rhee; 김영석; Young-seog Kim; 하일도; Il Do Ha (Ŭngyong tʻonggye yŏnʼgu, 2022)
본 논문에서는 최근 경주와 포항에서 심각한 피해를 주며 발생한 지진의 규모를 과거자료에 근거한 통계적 분석방법을 통해 예측하고자 한다. 이를 위해, 조선시대 역사지진 자료중에서 연단위 밀집도가 상대적으로 높은 1392~1771년의 5년 블록 최대 규모 자료를 이용하였다. 이 자료를 기반으로 일반화 극단값(generalized extreme value) 확률분포에 기초한 극단값 이론을 이용하여 조선시대 재현기간별 지진 규모 예측 및 분석을 제시하고자 한다. 일반화 극단값 분포의 모수추정을 위해 최대가능도추정법(maximum likelihood estimation, MLE)과 L-적률추정법(L-moments estimation, LME)을 사용한다. 특히 본 논문에서는 일반화 극단값 분포가 이러한 역사지진 자료에 대한 적절한 분석 모형이 될 수 있음을 적합도 검정(goodness-of-fit test)을 통해 보인다. In this paper, we predict the earthquake magnitudes which were recently occurred in Gyeongju and Pohang, using statistical methods based on historical data. For this purpose, we use the five-year block maximum data of 1392~1771 period, which has a relatively high annual density, among the historical earthquake magnitude data of the Chosun Dynasty. Then, we present the prediction and analysis of earthquake magnitudes for the return level over return period in the Chosun Dynasty using the extreme value theory based on the distribution of generalized extreme values (GEV). We use maximum likelihood estimation (MLE) and L-moments estimation for parameters of GEV distribution. In particular, this study also demonstrates via the goodness-of-fit tests that the GEV distribution can be an appropriate analytical model for these historical earthquake magnitude data.